Tracing the Remains of the Dutch Colonialism Period and Its Influence on Heritage Tourism Resources in Bandung City, Indonesia - Nugroho, Fajar Aditya; Handizar, Dhyana Hanifianti; Furqan, Alhilal (Archives of Business Research, 2023)
Relics of the past are the main attractions of heritage tourism, these past relics are not spared from the legacy of colonialism because of the implications that are still visible today. Such as in Bandung, where remnants of the colonialism period are still visible in urban elements that have been sustainable to this day. Therefore, this study aims to examine the legacy of Dutch colonialism in Bandung City and its influence on heritage tourism resources in Bandung in a descriptive qualitative manner through data collected through literature study. The results of this study indicate that the existence of colonialist values left behind in Bandung City has a major influence on the elements of tourism resources in Bandung City from the five dimensions, namely historical buildings and monuments; historical event sites; cultural sites and/or natural landscapes; language, literature, and music; and traditional Lifestyle.